High efficiency and stability of Au–Cu/hydroxyapatite catalyst for the oxidation of carbon monoxide. Issue 72 (22nd September 2017) - Guo, Jiuli; Yu, Huanhuan; Dong, Feng; Zhu, Baolin; Huang, Weiping; Zhang, Shoumin
Abstract : Synergistic effect between gold and CuO x phase for high efficiency and stability. Abstract : A highly efficient and stable Au–Cu/hydroxyapatite (HAP, Ca10 (PO4 )6 (OH)2 ) catalyst was reported. HAP was prepared through a deposition–precipitation method. Au–Cu/HAP catalysts were obtained by a two-step impregnation approach. The samples were characterized by XRD, TEM, SEM, UV-Vis, ICP, XPS, H2 -TPR, and O2 -TPD. CO oxidation reaction was carried out to evaluate the catalytic performance of samples. TEM and UV-Vis results showed that the metallic particles supported on Au–Cu/HAP were smaller than those on Au/HAP, and they were highly dispersed on the HAP support. Patterns of XPS revealed that CuO nanoparticles were formed in the Cu/HAP catalyst, while CuO and Cu2 O species coexisted in Au–Cu/HAP catalyst. Based on the O2 -TPD data, the addition of copper to Au/HAP gave rise to more new O2 adsorption sites and bigger O2 adsorption capacity. The catalysis results indicated that the Au–Cu/HAP was capable of obtaining higher efficiency and stability compared with Au/HAP and Cu/HAP for CO oxidation. It was likely that the synergistic interaction between gold and CuO x phase created the most active sites on Au–Cu/HAP and was responsible for the enhanced activity and stability in comparison with Au/HAP and Cu/HAP.